Cost-effectiveness analysis of trastuzumab deruxtecan in patients with HER2-low advanced breast cancer based on DESTINY-Breast04 - Zhan, Mei; Huang, Zijia; Xu, Ting; Xu, Xinyi; Zheng, Hanrui; Wu, Fengbo (Frontiers in Public Health, 2023)
Background and purpose Breast cancer is a rapidly raising healthcare problem worldwide. DESTINY-Breast04 demonstrated that trastuzumab deruxtecan (T-Dxd) had a survival advantage comparing to the physician's choice of chemotherapy for patients with HER2-low metastatic breast cancer. But at the same time, this expensive novel treatment also brought an economic burden. This study assessed the cost-effectiveness of T-Dxd based on results of DESTINY-Breast04 from the perspective of Chinese healthcare system. Materials and methods A three-state partitioned-survival model [progression-free survival (PFS), progressive disease (PD) and death] based on data from DESTINY-Breast04 and Chinese healthcare system was used to estimate the incremental cost-effectiveness ratio (ICER) of T-Dxd vs. the physician's choice of chemotherapy for HER2-low metastatic breast cancer. Costs, quality-adjusted life-years (QALYs) and the ICER in terms of 2022 US per QALY gained were calculated for both hormone receptor–positive cohort and all patients. One-way and probabilistic sensitivity analyses were performed to assess the model robustness. Results Compared with the physician's choice of chemotherapy, T-Dxd increased costs by 104,168.30, while gaining 0.31 QALYs, resulting in an ICER of 336,026.77 per QALY in all patients. The costs of T-Dxd and the utility of PFS were the crucial factors in determining the ICER. In the hormone receptor–positive cohort, the ICER was lower than that in all patients, with the ICER of 274,905.72 per QALY. The ICER was much higher than the commonly accepted willingness-to-pay threshold (357,96.83 per QALY). Conclusion T-Dxd as second- or subsequent-line treatment is not a cost-effective treatment option for HER2-low metastatic breast cancer from the perspective of the Chinese healthcare system.